Defined Contribution Pension Plans: Mutual Fund Asset Allocation Changes - Sialm, Clemens; Starks, Laura; Zhang, Hanjiang (American Economic Review, 2015)
In this paper we compare changes in asset allocations between mutual funds held in defined contribution pension plans and funds held by other investors. We investigate how flows into equity and fixed income mutual funds depend on macroeconomic conditions. We find that defined contribution plans react more sensitively to these conditions, suggesting effects on mutual fund managers and other investors.